OPTIMIZATION OF SMOOTHING PARAMETER BY KERNEL ESTIMATION OF PROBABILITY DENSITY DISTRIBUTION - Prokopenko, Igor; Martynchuk, Igor (Proceedings of National Aviation University, 2014)
In this paper the problem smoothing parameter choice for probability density kernel estimation isconsidered. The task of optimal smoothing parameter search according to predetermined criteria is formulated.